(untitled) (Nigerian Journal of Pharmaceutical Research, 2025)
Background: Insomnia is a mental health condition that affects an estimated one-third of the global population. The disorder can impact the social and economic activities of the sufferers. In sub-Saharan Africa including Nigeria, the magnitude of, and the socio-demographics associated with insomnia is rarely known. Objective: This study aimed to determine the prevalence of insomnia and the associated socio-demographics among ambulatory patients in Nigeria. Methods: This was a quantitative cross-sectional survey among consecutively sampled ambulatory adult patients aged 18 years and above at the General Outpatient clinics of the Olabisi Onabanjo University Teaching Hospital, Sagamu, Southwest Nigeria between January and June 2023. A 35-item structured questionnaire sectioned into three segments was used to evaluate the sociodemographic (section A), the medical and family history, and the living conditions of the respondents (Section B). Section C used the Athens Insomnia Scale (AIS) to evaluate insomnia. A Pearson Chi-square test was used to explore the association between insomnia and the socio-demographics of the respondents. A p-value <0.05 was considered statistically significant. Results: Of the 469 respondents, 127 (27.1%) were aged >65 years (mean age= 44.3±13.21 years), 299 (63.8%) were females and 198 (42.2%) had insomnia. Slightly above half of the respondents (52.6%) who had a family history of sleep disorder had insomnia in this study. Marital status (p=0.012), living arrangements (p=0.001), educational qualification (p=0.003) and the number of children in the family (p=0.007) were significantly associated with insomnia in this study. Conclusion: Insomnia is common among ambulatory adult patients in OOUTH, Sagamu Nigeria. Certain sociodemographic factors including living arrangements, educational qualification, number of children in the family and marital status are associated with insomnia in this population.